World Bank's SASKI - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
The World Bank´s Sustainable Agricultural Systems Knowledge and Institutions (SASKI) page on Markets and Agro-enterprises provides a guide to agricultural markets and agroenterprises.